(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
This study aimed to evaluate the effects of ursolic acid, hyperinsulinemia and vitamin B complex on sciatic nerve repair in diabetes mellitus male rabbits, determination of their effects on lipid profile and histological structures of the sciatic nerve. The results of our study showed that alloxan induced diabetes caused a significant increase (p<0.05) in serum cholesterol and triglyceride while treatment of extracted and standard ursolic acid, hyperinsulinemia and vitamin B complex caused a significant decrease (p<0.05) in serum cholesterol and triglyceride. There are significantly decreased (p<0.05) in serum high density lipoprotein (HDL) and significantly increase (p<0.05) in serum low density lipoprotein (LDL) is found in induced diabetic and hyperinsulinemia groups while there is a significant increase (p<0.05) of HDL in all treated groups except hyperinsulinemic group, on the other hand, there is a significant decrease (p<0.05) in LDL, especially in extracting ursolic acid group (p<0.05). Histological sections of sciatic nerve confirmed there is a degeneration of nerve fibers appears as areas of cloudy swelling and fatty de- generation of the nerve fibers due to nerve crush. There are various improvement changes due to the different treatment type.